2015
DOI: 10.1007/s10658-015-0721-9
|View full text |Cite
|
Sign up to set email alerts
|

Induction of defence responses by cinnamomins against Phytophthora cinnamomi in Quercus suber and Quercus ilex subs. rotundifolia

Abstract: The strong association between Phytophthora cinnamomi and the mortality and decline of Quercus suber and Q. ilex subsp. rotundifolia has been known for two decades. The ability of elicitins secreted by this pathogen to trigger defence responses in these Quercus against itself was evaluated in this work. Biomass quantification by quantitative real-time PCR revealed a significant decrease in pathogen colonization of Q. suber roots after 24 h pre-treatment with α-and β-cinnamomin. In Q. suber and Q. ilex roots pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Similar results were also reported by Amaral et al, (2008) in coffee plants. Several authors also observed pathogenic structures (hyphae and oospores) in holm oak, Quercus suber (Ruiz-Gómes et al, 2015) and Quercus ilex (Ebadzad et al, 2015) infected with P. cinnamomi. These findings are in accordance with the studies of Oh and Hensen (2007) in oregon ceder plants and Monteiro et al, (2017) in chestnut plants, who observed the presence of oospores inside phloem and xylem cells in non Si-fertilized plants (0 mM SiK ® ) and a very lower number in Si-treated plants (10 mM SiK ® , Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Similar results were also reported by Amaral et al, (2008) in coffee plants. Several authors also observed pathogenic structures (hyphae and oospores) in holm oak, Quercus suber (Ruiz-Gómes et al, 2015) and Quercus ilex (Ebadzad et al, 2015) infected with P. cinnamomi. These findings are in accordance with the studies of Oh and Hensen (2007) in oregon ceder plants and Monteiro et al, (2017) in chestnut plants, who observed the presence of oospores inside phloem and xylem cells in non Si-fertilized plants (0 mM SiK ® ) and a very lower number in Si-treated plants (10 mM SiK ® , Fig.…”
Section: Discussionmentioning
confidence: 94%
“…In our study, elicited holm oak somatic embryos did not inhibit Phytophthora cinnamomi mycelium growth in dual culture tests, being the plates with somatic embryos elicited with PFE-50, 50 µM BTH, 5, 10 or 50 µM MeJA and 5 µM PABA those showing ratios higher than 1 between growth towards control and growth towards elicited material at the end of the experiment. Treatments with cinnamomin have been reported to inhibit oomycete root colonization in holm oak 21 ; foliar applications of a BTH derivate also reduced the incidence of oomycete root infection in several forest 28 ; MeJA have been referred to induce resistance in conifers seedlings to a pathogenic oomycete 46 and pests 47 49 , as well as resistance to pathogens in plants such as arabidopsis 50 , grapevine 51 or tomato 37 , and in harvested fruits as bayberries 52 and grapes 53 , 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Plants respond to oomycete infection by multiple defense mechanisms, including strengthening of physical barriers, production of antimicrobial molecules, and programmed cell death 19 . In addition, many biological and chemical elicitors, such as necrotizing pathogens, salicylic acid (SA), benzothiadiazole (BTH), and methyl jasmonate (MeJA), have been reported to activate plant immune response to pathogens [20][21][22][23] . These elicitors cause the induction of a primed state of enhanced defenses which allows plants to display either faster, stronger, or both, activation of the defense responses after further attacks by pathogens or insects, and also under abiotic stress conditions 24 .…”
mentioning
confidence: 99%
“…Plant recognition of cinnamomin contributes to the induction of host defence responses. Pretreatment of oak (Q. suber or Q. ilex) or chestnut (C. sativa) roots with a-or b-cinnamomin results in a significant reduction in root colonization by P. cinnamomi (Ebadzad et al, 2015;Maia et al, 2008;Medeira et al, 2012). Further studies of the role of cinnamomins in Phytophthora-plant interactions may be aided by the development of an improved method for the production and purification of b-cinnamomin (Hofzumahaus and Schallmey, 2013).…”
Section: Effectors and Elicitorsmentioning
confidence: 99%